Environment-Dependent Heterosis and Transgressive Gene Expression in Reciprocal Hybrids between the Channel Catfish Ictalurus punctatus and the Blue Catfish Ictalurus furcatus - Haolong Wang; Timothy J. Bruce; Baofeng Su; Shangjia Li; Rex A. Dunham; Xu Wang (Biology, 2022)
The hybrid between female channel catfish (Ictalurus punctatus) and male blue catfish (Ictalurus furcatus) is superior in feed conversion, disease resistance, carcass yield, and harvestability compared to both parental species. However, heterosis and heterobeltiosis only occur in pond culture, and channel catfish grow much faster than the other genetic types in small culture units. This environment-dependent heterosis is intriguing, but the underlying genetic mechanisms are not well understood. In this study, phenotypic characterization and transcriptomic analyses were performed in the channel catfish, blue catfish, and their reciprocal F1s reared in tanks. The results showed that the channel catfish is superior in growth-related morphometrics, presumably due to significantly lower innate immune function, as investigated by reduced lysozyme activity and alternative complement activity. RNA-seq analysis revealed that genes involved in fatty acid metabolism/transport are significantly upregulated in channel catfish compared to blue catfish and hybrids, which also contributes to the growth phenotype. Interestingly, hybrids have a 40–80% elevation in blood glucose than the parental species, which can be explained by a phenomenon called transgressive expression (overexpression/underexpression in F1s than the parental species). A total of 1140 transgressive genes were identified in F1 hybrids, indicating that 8.5% of the transcriptome displayed transgressive expression. Transgressive genes upregulated in F1s are enriched for glycan degradation function, directly related to the increase in blood glucose level. This study is the first to explore molecular mechanisms of environment-dependent heterosis/heterobeltiosis in a vertebrate species and sheds light on the regulation and evolution of heterosis vs. hybrid incompatibility.